Structural response of ferrocement panels incorporating lightweight expanded clay and perlite aggregates: Experimental, theoretical and statistical analysis. (1st June 2019) - Madadi, Amirhossein; Tasdighi, Mahdi; Eskandari-Naddaf, Hamid
Highlights: Structural response of lightweight ferrocement panels (FPs) is investigated. Behavior of 21 FPs is evaluated experimentally, theoretically and statistically. Proposed theoretical method can predict behavior of FPs with a reasonable accuracy. The optimal values of design parameters are obtained using Taguchi method. Taguchi can determine the influential parameters on structural response of FPs. Abstract: Structural response of lightweight ferrocement panels (FPs) as low cost, durable, thin engineering elements was evaluated. Specifically, 21 FPs incorporating different contents of lightweight expanded clay (leca) (i.e. 40, 20, and 10 vol%) and perlite (i.e. 55, 35, and 15 vol%) aggregates and different number of expanded rib lath (ERL) layers (i.e. 1, 2 and 3) were constructed and subjected to three-point flexure test. Further, experimental and theoretical results of first crack (Fcr ) and ultimate (Fu ) loads were compared against each other by means of load-deflection curves. A statistical analysis was also performed using Taguchi method to obtain the optimal value and contribution of influential factors. The results indicated that the mean values of Fcr and Fu were higher at the FPs incorporating leca and perlite, respectively. In addition, the values of deflection at first crack ( D F c r ) and ultimate ( D F u ) loads for the FPs incorporating leca were lower than those of FPs incorporating perlite by about 13% and 31%, respectively, leading to a higher ductility index (DI) for the FPs incorporating perlite. Comparing the behavior of lightweight and normal FPs revealed that the DIs of the leca- and perlite-incorporated FPs were about 21% lower and 5% higher than normal FPs, respectively. The results of the statistical analysis showed that the volume content of lightweight aggregates provided higher contribution to improve the Fcr of the FPs, while the number of ERL layers was a more influential factor on improving the Fu and controlling the D F c r and D F u of the FPs.